Nursing workforce deployment and intensive care unit strain during the COVID-19 pandemic in Victoria, Australia. Issue 1 (January 2023) - Topple, Michelle; Jaspers, Rose; Watterson, Jason; McClure, Jason; Rosenow, Melissa; Pollock, Wendy; Pilcher, David
Abstract: Background: The COVID-19 pandemic demanded intensive care units (ICUs) globally to expand to meet increasing patient numbers requiring critical care. Critical care nurses were a finite resource in this challenge to meet growing patient numbers, necessitating redeployment of nursing staff to work in ICUs. Objective: Our aim was to describe the extent and manner by which the increased demand for ICU care during the COVID-19 pandemic was met by ICU nursing workforce expansion in the late 2021 and early 2022 in Victoria, Australia. Methods: This is a retrospective cohort study of Victorian ICUs who contributed nursing data to the Critical Health Information System from 1 December 2021 to 11 April 2022. Bedside nursing workforce data, in categories as defined by Safer Care Victoria's pandemic response guidelines, were analysed. The primary outcome was 'insufficient ICU skill mix'—whenever a site had more patients needing 1:1 critical care nursing care than the mean daily number of experienced critical care nursing staff. Results: Overall, data from 24 of the 47 Victorian ICUs were eligible for analysis. Insufficient ICU skill mix occurred on 10.3% (280/2725) days at 66.7% (16/24) of ICUs, most commonly during the peak phase from December to mid-February. The insufficient ICU skill mix was more likely to occur when there were more additional ICU beds open over the 'business-as-usual' number. Counterfactual analysis suggested that had there been no redeployment of staff to the ICU, reduced nursing ratios, with inability to provide 1:1 care, would have occurred on 15.2% (415/2725) days at 91.7% (22/24) ICUs. Conclusion: The redeployment of nurses into the ICU was necessary. However, despite this, at times, some ICUs had insufficient staff to cope with the number and acuity of patients. Further research is needed to examine the impact of ICU nursing models of care on patient outcomes and on nurse outcomes.